Parental Involvement in Social Support (A Case Study of Bullying Victims Among Junior High School Students Reported to the Integrated Police Service Center (SPKT) of Palembang Police Department) - Riansyah, Khaidir; Almigo, Nuzsep (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to examine parental involvement in providing social support to bullying victims among junior high school students who reported cases to the Integrated Police Service Center (SPKT) of Palembang Metropolitan Resort Police (Polrestabes Palembang). The research addresses the critical need to understand how parental support influences the psychological recovery of children experiencing bullying. Method: The research employed qualitative observation method to gain in-depth understanding of emotional development and communication patterns of children who are victims of bullying. Practical Applications: The observation was conducted in a private room at SPKT after the victim completed the suspect report form, focusing on social interactions, facial expressions, emotional responses, and daily communication skills. Conclusion: Bullying has serious psychological impacts on victims, including anxiety, depression, and suicidal thoughts. Victims tend to withdraw and feel isolated. Polrestabes Palembang has implemented educational outreach and counseling in schools to prevent and address bullying cases. Parental involvement proves crucial as a protective factor in children's recovery process.